A ready-to-use and wipe-on composite coating for anti-ultraviolet radiation

By developing an ready-to-use, rub-proof UV radiation composite coating, the problem that existing cell culture plates cannot effectively shield UV radiation is solved, independent irradiation of each cell culture well is achieved, the accuracy of experimental results is improved, and the coating is also applied. The easy-to-removal properties reduce interference to subsequent experiments.

CN116904099BActive Publication Date: 2025-02-11THE FIRST HOSPITAL OF CHINA MEDICIAL UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311104417.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-11
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

The existing transparent cell culture plates cannot effectively shield the ultraviolet radiation, causing the irradiation schemes of adjacent cell culture wells to interfere with each other, affecting the accuracy of the experimental results.

Method used

Develop an ready-to-use, wipe-proof UV radiation composite coating to form a uniform thin layer through spraying, with good film-forming properties and strong UV absorption properties, and is easy to tear off as a whole after drying, avoiding interference to subsequent experiments.

Benefits of technology

Effectively shield UV radiation, ensure independent irradiation scheme for each cell culture well, improve the accuracy of experimental results, and the easy tear-off properties of the paint reduce interference to subsequent experiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the field of material technology, and relates to a composite coating for preventing ultraviolet radiation that can be used and wiped off. The composite coating comprises the following components in parts by weight: 15 to 35 parts of polyurethane-1, 15 to 35 parts of polyacrylic acid, 2 to 8 parts of graphene particles, 2 to 8 parts of phenoxyethanol, 0.2 to 0.4 parts of lead particles, 0.2 to 0.4 parts of magnesium particles, 0.2 to 0.4 parts of aluminum carbonate particles, 1 to 2 parts of emulsifiers, and 60 to 80 parts of deionized water. The composite coating for preventing ultraviolet radiation that can be used and wiped off designed by the present invention is convenient for modeling with ultraviolet radiation of cell culture. The coating has good film-forming properties, excellent water resistance, strong ultraviolet absorption properties, and is easy to tear off as a whole after drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a ready-to-use and wipe-on anti-ultraviolet radiation composite coating. Background Art

[0002] Solar ultraviolet radiation is of great significance to human life activities, and also affects the progression of diseases and the aging process. In in vitro experiments, researchers often need to irradiate cells cultured in vitro with ultraviolet radiation to model photoaging and photodamage, in order to simulate natural irradiation and damage; however, in in vitro cell culture experiments, different intervention methods and irradiation schemes may be required between each cell culture well, and the current finished cell culture plates are mostly made of transparent materials, which cannot shield ultraviolet rays and cannot avoid mutual interference between irradiation schemes of adjacent cell culture wells, affecting the accuracy of the experimental results.

[0003] Ultraviolet shielding (absorption) agents can improve the shielding and absorption capacity of materials for ultraviolet light. Adding ultraviolet shielding agents to materials and utilizing their shielding and absorption performance characteristics can greatly reduce the mutual interference of irradiation schemes of adjacent cell culture wells, ensure the independence of irradiation schemes for each well, and ensure the accuracy of the results. At the same time, in order to adapt to subsequent experimental operations such as immunofluorescence and oscillating slices, ultraviolet shielding (absorption) agents suitable for cell culture plates are preferably easy to attach to the surface of finished cell culture plates in the form of spraying, etc., and easy to remove by non-organic solvents after ultraviolet irradiation, and not easy to leave fine and thin layers of coatings, so as to reduce interference with subsequent experimental operations and result analysis. Therefore, it is very necessary to develop a ready-to-use and wipe-on anti-ultraviolet radiation composite coating for the standardization and standardization of experiments and the repeatability of conclusions. Summary of the invention

[0004] Based on the problems existing in the above-mentioned prior art, the present invention aims to propose a composite coating that can be used and wiped off to prevent ultraviolet radiation. Ultraviolet radiation belongs to short-wave radiation, and ultraviolet shielding (absorbing) agents can effectively reduce its transmission and play a shielding role. In order to meet the experimental needs of in vitro cell culture, the present invention designs a composite coating that can be used and wiped off to prevent ultraviolet radiation, which is convenient for modeling with ultraviolet radiation of cell culture. This coating has good film-forming properties, excellent water resistance, strong ultraviolet absorption properties, and is easy to tear off as a whole after drying.

[0005] This coating can be easily formed into a uniform thin layer by spraying. After solidifying into a film on the cell plate, it can effectively shield ultraviolet radiation. At the same time, after the experiment, the thin layer of coating can be easily torn off as a whole. There is no need to use organic solvents such as ethanol, acetone, and xylene to dissolve and wipe it by chemical means. The thin layer of coating can be peeled off by simply tearing it off with bare hands.

[0006] To achieve the above objectives, the present invention adopts the following technical solutions.

[0007] A composite coating for preventing ultraviolet radiation that can be used and wiped on immediately comprises the following components in parts by weight: 15 to 35 parts of polyurethane-1, 15 to 35 parts of polyacrylic acid, 2 to 8 parts of graphene particles, 2 to 8 parts of phenoxyethanol, 0.2 to 0.4 parts of single lead particles, 0.2 to 0.4 parts of single magnesium particles, 0.2 to 0.4 parts of aluminum carbonate particles, 1 to 2 parts of emulsifier and 60 to 80 parts of deionized water.

[0008] Further, micro-particle copolymerization is performed to prepare the micro-particles. Specifically, vortexing is performed for 1-1.5 minutes, standing for 0.5-1 minutes, vortexing for 1-1.5 minutes, and this cycle is repeated 3-5 times.

[0009] Furthermore, the particle size of graphene particles is 10 to 30 micrometers, the particle size of lead particles is 200 to 400 nanometers, the particle size of magnesium particles is 200 to 400 nanometers, and the particle size of aluminum carbonate particles is 300 to 600 nanometers.

[0010] Compared with the prior art, the beneficial effects of the present invention are as follows.

[0011] 1. The emulsion prepared by the present invention has better film-forming properties, superior water resistance and strong ultraviolet absorption properties than the redispersible latex powder prepared by the previous technology. In addition, the coating is easy to dry, forms a uniform film after quick drying, and is easy to be torn off as a whole. It can be widely used in ultraviolet shielding functional coatings and zero-VOC environmentally friendly coatings, especially suitable for anti-ultraviolet spraying of cell culture plates.

[0012] 2. The ratio combination of polyurethane-1, polyacrylic acid and phenoxyethanol ensures that the coating forms a uniform film after quick drying, the film is water-resistant, and the structure is strong and easy to be torn off as a whole; the combination of lead element, magnesium element and aluminum carbonate particles has excellent ultraviolet shielding and absorption performance; graphene particles can not only shield ultraviolet radiation, but its strong light-absorbing properties also give the coating the ability to absorb visible light.

[0013] 3. Existing coatings are difficult to remove after drying and are not suitable for spraying on cell culture plates, especially after irradiation, the spray coating is difficult to remove. The coating scheme designed and summarized in this method not only has the properties of easy film formation, water resistance, and strong ultraviolet absorption, but is also easy to tear off after drying and forming a film, which is convenient for various needs of in vitro cell culture ultraviolet radiation modeling, especially for subsequent microscopic staining observation experiments. DETAILED DESCRIPTION

[0014] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0015] A composite coating for preventing ultraviolet radiation that can be used and wiped on immediately comprises the following components in parts by weight: 15 to 35 parts of polyurethane-1, 15 to 35 parts of polyacrylic acid, 2 to 8 parts of graphene particles, 2 to 8 parts of phenoxyethanol, 0.2 to 0.4 parts of single lead particles, 0.2 to 0.4 parts of single magnesium particles, 0.2 to 0.4 parts of aluminum carbonate particles, 1 to 2 parts of emulsifier and 60 to 80 parts of deionized water.

[0016] Further, micro-particle copolymerization is performed to prepare the micro-particles. Specifically, vortexing is performed for 1-1.5 minutes, standing for 0.5-1 minutes, vortexing for 1-1.5 minutes, and this cycle is repeated 3-5 times.

[0017] Furthermore, the particle size of graphene particles is 10 to 30 micrometers, the particle size of lead particles is 200 to 400 nanometers, the particle size of magnesium particles is 200 to 400 nanometers, and the particle size of aluminum carbonate particles is 300 to 600 nanometers.

[0018] Example 1.

[0019] A ready-to-use and ready-to-wipe UV radiation-proof composite coating is prepared by micronizing and copolymerizing, and the specific steps are as follows:

[0020] Step 1, 35 parts of polyurethane-1, 30 parts of polyacrylic acid, 4 parts of graphene particles, 2 parts of phenoxyethanol, 0.4 parts of lead particles, 0.2 parts of magnesium particles, 0.2 parts of aluminum carbonate particles, 1.2 parts of emulsifier and 60 parts of deionized water are mixed to obtain a mixed slurry;

[0021] Step 2: vortex the mixed slurry obtained in step 1 for 1 minute, let it stand for 0.5 minutes, and vortex it for 1 minute, and repeat this process 5 times to obtain the final ready-to-use and wipe-on UV radiation protection composite coating.

[0022] After spraying with the ready-to-use anti-ultraviolet radiation composite coating (thickness of about 0.05mm), the light board + culture dish strength test, the irradiation intensity is 0 mW / cm3 three times 2 , five times: 0.01 mW / cm 2 ; The drying film-forming time of this coating is 10s; after film formation, the coating is evenly attached to the smooth surface and is easy to tear off, which can meet the needs of laboratory use. After spraying and removal, the background noise caused by the strip-like residual coating photographed using a phase contrast microscope is smaller than that of traditional black organic coatings, and has less impact on shooting; at the same time, when using a fluorescence microscope to shoot, the residual coating has less impact on the overexposure of indicators and the consistency of the color card than traditional black organic coatings.

[0023] After spraying the ready-to-use and wipe-off anti-ultraviolet radiation composite coating of Example 1 (thickness of about 0.05 mm) and wiping it off with an organic solvent (anhydrous ethanol), the light board + culture dish strength test was carried out using eight different irradiation intensities for irradiation and comparison with the existing black organic coating. The eight groups of data are shown in Figure 1, which proves that the coating structure is strong and easy to be torn off as a whole.

[0024] Table 1 Comparison of irradiation intensity after wiping between existing coatings and the coating of Example 1.

[0025]

[0026] Example 2.

[0027] A ready-to-use and ready-to-wipe anti-ultraviolet radiation composite coating is prepared by micronizing and copolymerizing, and the specific steps are:

[0028] Step 1, 30 parts of polyurethane-1, 35 parts of polyacrylic acid, 4 parts of graphene particles, 4 parts of phenoxyethanol, 0.4 parts of lead particles, 0.2 parts of magnesium particles, 0.4 parts of aluminum carbonate particles, 2 parts of emulsifier and 75 parts of deionized water are mixed;

[0029] Step 2: vortex the mixed slurry obtained in step 1 for 1 minute, let it stand for 1 minute, and vortex it for 1 minute, and repeat this process 5 times to obtain the final ready-to-use and wipe-on UV radiation protection composite coating.

[0030] After spraying with the ready-to-use and wipe-off anti-ultraviolet radiation composite coating (thickness is about 0.03mm), the light board + culture dish intensity test was carried out, and the irradiation intensity was 0.01 mW / cm2 four times and 0.02 mW / cm2 four times; the drying film-forming time of this coating is 15s; after film formation, the coating is evenly attached to the smooth surface and is easy to tear off, which can meet the needs of laboratory use. After spraying and removal, the background noise caused by the strip-like residual coating photographed using a phase contrast microscope is smaller than that of traditional black organic coatings, and has less impact on shooting; at the same time, when using a fluorescent microscope to shoot, the residual coating has less impact on the overexposure of indicators and the consistency of the color card than traditional black organic coatings.

[0031] After spraying the ready-to-use and wipe-off anti-ultraviolet radiation composite coating of Example 2 (thickness of about 0.05 mm) and wiping it off with an organic solvent (anhydrous ethanol), the light board + culture dish strength test was carried out using eight different irradiation intensities for irradiation and comparison with the existing black organic coating. The eight groups of data are shown in Figure 2, which proves that the coating structure is strong and easy to be torn off as a whole.

[0032] Table 2 Comparison of irradiation intensity after wiping between the existing coating and the coating of Example 2.

[0033]

[0034] Example 3.

[0035] A ready-to-use and ready-to-wipe UV radiation-proof composite coating is prepared by micronizing and copolymerizing, and the specific steps are as follows:

[0036] Step 1, 25 parts of polyurethane-1, 25 parts of polyacrylic acid, 5 parts of graphene particles, 6 parts of phenoxyethanol, 0.3 parts of lead particles, 0.3 parts of magnesium particles, 0.3 parts of aluminum carbonate particles, 2 parts of emulsifier and 70 parts of deionized water are mixed to obtain a mixed slurry;

[0037] Step 2: vortex the mixed slurry obtained in step 1 for 1.5 minutes, let it stand for 0.5 minutes, and vortex it for 1.5 minutes, and repeat this process for 5 times to obtain the final ready-to-use and wipe-on UV radiation protection composite coating.

[0038] After spraying with the ready-to-use and wipe-off anti-ultraviolet radiation composite coating (thickness of about 0.1mm), the light board + culture dish intensity test showed that the irradiation intensity was 0 mW / cm2; the drying and film-forming time of this coating is 10s; after film formation, the coating is evenly attached to the smooth surface and is easy to tear off, which can meet the needs of laboratory use. The background noise caused by the strip-like residual coating photographed using a phase contrast microscope after spraying and removal is smaller than that of traditional black organic coatings, and has less impact on shooting; at the same time, when using a fluorescent microscope to shoot, the residual coating has less impact on the overexposure of indicators and the consistency of the color card than traditional black organic coatings.

[0039] After spraying the ready-to-use and wipe-off anti-ultraviolet radiation composite coating of Example 3 (thickness of about 0.05 mm) and wiping it off with an organic solvent (anhydrous ethanol), the light board + culture dish strength test was carried out using eight different irradiation intensities for irradiation and comparison with the existing black organic coating. The eight groups of data are shown in Figure 3, which proves that the coating structure is strong and easy to be torn off as a whole.

[0040] Table 3 Comparison of irradiation intensity after wiping between the existing coating and the coating of Example 3.

[0041]

[0042] Comparative example 1.

[0043] 30 parts of polyacrylic acid, 4 parts of graphene particles, 2 parts of phenoxyethanol, 0.4 parts of lead particles, 0.2 parts of magnesium particles, 0.2 parts of aluminum carbonate particles, 1.2 parts of emulsifier and 60 parts of deionized water were mixed to obtain a mixed slurry. The remaining steps were the same as in Example 1.

[0044] The coating film is uneven and the structure is not solid. The background noise caused by the residual coating after spraying and removal is increased by using a phase contrast microscope, which has a greater impact on subsequent shooting. At the same time, when using a fluorescence microscope to shoot, the residual coating causes uneven exposure of indicators and increased heterogeneity of color cards, which interferes with subsequent indicator analysis.

[0045] Comparative example 2.

[0046] Mix 25 parts of polyurethane-1, 25 parts of polyacrylic acid, 5 parts of graphene particles, 0.3 parts of lead particles, 0.3 parts of magnesium particles, 0.3 parts of aluminum carbonate particles, 2 parts of emulsifier and 70 parts of deionized water to obtain a mixed slurry. The remaining steps are the same as Example 3.

[0047] The drying film-forming time is prolonged to 40s; at the same time, the difficulty of removal increases, and residual fragments are produced after tearing off.

[0048] Comparative example 3.

[0049] Mix 35 parts of polyurethane-1, 30 parts of polyacrylic acid, 2 parts of phenoxyethanol, 0.4 parts of lead particles, 0.2 parts of magnesium particles, 0.2 parts of aluminum carbonate particles, 1.2 parts of emulsifier and 60 parts of deionized water to obtain a mixed slurry; the remaining steps are the same as in Example 1.

[0050] Table 4 Comparison of irradiation intensity after coating spraying between Comparative Example 3 and Example 1.

[0051]

Claims

1. A ready-to-use and rub-on UV radiation protection composite coating, characterized in that: The invention comprises the following components in parts by weight: 15 to 35 parts of polyurethane-1, 15 to 35 parts of polyacrylic acid, 2 to 8 parts of graphene particles, 2 to 8 parts of phenoxyethanol, 0.2 to 0.4 parts of single lead particles, 0.2 to 0.4 parts of single magnesium particles, 0.2 to 0.4 parts of aluminum carbonate particles, 1 to 2 parts of emulsifier and 60 to 80 parts of deionized water.

2. A ready-to-use and rub-on UV radiation protection composite coating, characterized in that: The invention comprises the following components in parts by weight: 35 parts of polyurethane-1, 30 parts of polyacrylic acid, 4 parts of graphene particles, 2 parts of phenoxyethanol, 0.4 parts of lead particles, 0.2 parts of magnesium particles, 0.2 parts of aluminum carbonate particles, 1.2 parts of emulsifier and 60 parts of deionized water.

3. A ready-to-use and rub-on UV radiation protection composite coating, characterized in that: The invention comprises the following components in parts by weight: 30 parts of polyurethane-1, 35 parts of polyacrylic acid, 4 parts of graphene particles, 4 parts of phenoxyethanol, 0.4 parts of lead particles, 0.2 parts of magnesium particles, 0.4 parts of aluminum carbonate particles, 2 parts of emulsifier and 75 parts of deionized water.

4. A ready-to-use and rub-on UV radiation protection composite coating, characterized in that: The invention comprises the following components in parts by weight: 25 parts of polyurethane-1, 25 parts of polyacrylic acid, 5 parts of graphene particles, 6 parts of phenoxyethanol, 0.3 parts of lead particles, 0.3 parts of magnesium particles, 0.3 parts of aluminum carbonate particles, 2 parts of emulsifier and 70 parts of deionized water.

5. The ready-to-use and wipe-on anti-ultraviolet radiation composite coating according to any one of claims 1 to 4, characterized in that: The composite coating is prepared by micronized copolymerization. Specifically, the mixture is vortexed for 1-1.5 minutes, allowed to stand for 0.5-1 minutes, vortexed for 1-1.5 minutes, and the process is repeated 3-5 times.

6. The ready-to-use and wipe-on UV radiation protection composite coating according to any one of claims 1 to 4, characterized in that: The particle size of the graphene particles is 10 to 30 micrometers; the particle size of the lead single substance particles is 200 to 400 nanometers; the particle size of the magnesium single substance particles is 200 to 400 nanometers; and the particle size of the aluminum carbonate particles is 300 to 600 nanometers.

Citation Information

Patent Citations

  • Improved ultraviolet-proof coating and preparation method thereof

    CN105440922A

  • Coating composition capable of absorbing UV radiation

    CN1639279A